Pengaruh Strategi True Or False Terhadap Hasil Belajar Siswa pada Mata Pelajaran Fiqih di MTss Proyek Kandepag Medan - Siti Rifani; Selamat Pohan (EduInovasi: Journal of Basic Educational Studies, 2024)
ln education, achieving learning goals with good Iearning outcomes is a driving force that motivates individuals to do it optimally, and it is one of the desires that must be fulfilled. ln order to achieve learning goals, teachers are also required to understand and choose strategies, methods, or media that are engaging for students to implement. This is because several research studies have shown a positive relationship between learning strategies and students' learning achievements, with the frequency of using learning strategies significantly predicting academic performance or student achievement. Therefore, this study aims to determine the influence of the true or false strategy on students' learning outcomes in the subject of Fiqh in class VIII of MTSS Proyek Kandepag Medan. The method used in this study is quantitative research with quasi-experimental research data analysis, using a non-equivalent controi group design. The sampling technique used as purposive sampling, with two research samples, namely class VIII A (Control Class) and VlIl B (Experimental Class), the research instrument used was a test instrument consisting of 20 true or false statements. The research results found an average with the control class of 55.32, while the experimental class obtained an average of 79.86, so in this case, the true or false strategy influences the learning outcomes of students in the Fiqh subject.